Effect of multi-pronged interventions in reducing low birth weight and maternal anaemia among pregnant women. A community-based interventions research in non-agrarian resource constrained setting of rural Pakistan - Inayat Thaver; Ahsan Maqbool Ahmad; Mariam Ashraf; Syed Kamal Asghar; Muhammad Sarwat Mirza (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To investigate the effect on maternal and infant health of iron plus folate and multiple micronutrient supplements, along with deworming and health education session provided to pregnant women in rural, non-agrarian and food-insecure areas. Methods: The quasi-experimental study was conducted in Tharparker and Umerkot districts, Sindh, Pakistan, in 2013-14, and comprised pregnant women in their earlier weeks of pregnancy. The enrolment and follow-up phase entailed 3 visits to each subject. Areas covered by lady health workers were designated as intervention areas, and those with non-LHW population were labelled as non-intervention areas. Results: Of the 1204 subjects, 600(49.8%) were in the intervention group and 604(50.2%) were in the non-intervention group. By the end of the follow-up phase, significantly more women had increased number of meals in the intervention group compared to the non-intervention group (p<0.001). There was a significantly higher increase in mean haemoglobin levels and body mass index of women in the intervention arm after 3 and 6 months of interventions (p<0.05). Significantly higher mean birth weight was recorded in intervention areas compared to non-intervention areas (p<0.05). Conclusion: Community-based provision of multiple micronutrients to women along with deworming, health education and dietary counselling significantly reduced the prevalence of anaemia and reduced the incidence of low birth weight. Key Words: Maternal anaemia, Low birth weight, Multiple micronutrients, Nutrition. Continuous...